25 Americans : Painting in the 90s. - Sobel, Dean (Milwaukee : MAM (Milwaukee Art Museum), 1995)
Applebroog, Ida ; Cruz Azaceta, Luis ; Burton, Richmond ; Cain, Peter ; Close, Chuck ; Currin, John ; Fischl, Eric ; Fishman, Louise ; Gerber, Gaylen ; Golub, Leon ; Grabner, Michelle ; Heilmann, Mary ; Kim, Byron ; Ledgerwood, Judy ; Ligon, Glenn ; Mangold, Robert ; Murray, Elizabeth ; Nelson, Dona ; Pittman, Lari ; Rothenberg, Susan ; Steir, Pat ; Taaffe, Philip ; Williams, Sue ; Winters, Terry ; Wool, Christopher
Checklist + biog. p. 29-31
Engels
25 Americans : Painting in the 90s, MAM (Milwaukee Art Museum) Milwaukee, September 8 - November 5, 1995
boek
Keywords: Amerika